Pengaruh Pertumbuhan Ekonomi, Suku Bunga SIBOR, dan Kurs Mata Uang terhadap Investasi Asing Langsung di Indonesia Tahun 2008-2022 - Nicholas Devlin Wijaya Damanik; M.Taufiq (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Foreign investment plays a very important role in the economic growth of a country, especially in developing countries in the current era of globalization. Economic growth, SIBOR (Singapore Interbank Offer Rate), and currency exchange rates are considered to have an influence in determining the level of foreign direct investment. This study aims to determine the significance of the influence of economic growth, SIBOR interest rates, and currency exchange rates on foreign direct investment in Indonesia in the period 2008-2022. By using quantitative analysis method, namely multiple linear regression analysis and the data used are 15 data from each variable. The results of this study show that economic growth has a positive and significant effect, SIBOR interest rates have no significant effect, and currency exchange rates have a negative and significant effect on foreign direct investment in Indonesia.